Am Newid - Edwards, Dana (Y Lolfa, 2017)
A contemporary, easy-to-read novel which aims at getting to grips with our attitudes towards those who do not conform with our ideas re tradition. Ceri returns to her childhood home, a very different person to the one who left many years ago. Intro – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – 11 – 12 – 13 – 14 – 15 – 16.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books